SOCIO-PSYCHOLOGICAL DETERMINANTS OF MANAGERIAL DECISION-MAKING WITHIN THE FRAMEWORK OF ORGANIZATIONAL COMMUNICATION - Azamat S. Nazarov (Western European Studies, 2025)
Managerial decision-making is a central process in organizational effectiveness and leadership performance, particularly within complex communication environments. This article explores the socio-psychological determinants that influence managerial decisionmaking in the context of organizational communication. Drawing on theories of social influence, group dynamics, trust, and communication psychology, the study analyzes how interpersonal interactions, information exchange, and organizational climate shape the quality and effectiveness of managerial decisions
Keywords: managerial psychology; decision-making; social-psychological factors